A simulation model of a multi-server EJB system. - Mc Guinness, David (Software engineering notes.)
Despite the fact that EJB (Enterprise Java Beans) is a widely used technology, research in the area of performance modelling of EJB application servers is quite sparse. This paper will describe how Workbench?, an advanced simulation modelling tool, can be used to build a scalable model of a multi-server EJB system that allows users to input variables that describe interactions and their constituent methods, as well as system parameters. The model will output the average time for each given user interaction and allow users to seek system improvements by changing the system parameters and workloads.